Additions to the herpetofauna of Hon Son Island, Rach Gia Bay, Kien Giang Province, southern Vietnam with a discussion of syntopy between the granite cave-adapted Bent-toed Gecko Cyrtodactylus eisenmanae and a new Cyrtodactylus of uncertain taxonomic status - Grismer, L. Lee; Smith, Jacob (Zootaxa, 2023)
An updated herpetofaunal checklist of Hon Son Island, Rach Gia Bay, Kien Giang Province, southern Vietnam is presented which reports of new records for Kaloula pulchra, Sylvirana cf. mortenseni, Cyrtodactylus sp., and Gehyra mutilata bringing the island total to 21 species. Cyrtodactylus sp. is an unidentified granite-cave adapted species that occurs in syntopy with the granite-cave adapted C. eisenmanae, bringing the total number of Cyrtodactylus on this tiny island (11.5 km2) to three. The implications of highly specialized syntopic congeneric ecomorphs is discussed.